The Effectiveness of the Career Story Interview from the Perspective of Life Designing - Di Fabio, Annamaria (South African Journal of Higher Education, 2016)
The aim of the study under discussion was to evaluate the effectiveness of Savickas’ (2010) Career Story Interview in a group of Italian university students. The study was conducted according to Rehfuss’ (2009) Future Career Autobiography and from the perspective of Life Designing for the 21st century. It included an experimental group, which received a Career Story Interview intervention, and a control group. A comparison of the initial Future Career Autobiographies (FCAs) with the subsequent FCAs indicated that the members of the experimental group had more specific life and occupational goals after the intervention thus underlining the effectiveness of the Career Story Interview.